THE CONCEPT OF HUMAN AND ITS IMPLICATIONS FOR ISLAMIC EDUCATION - Siti Yumnah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
The desire to discuss humans will definitely never run out and always develop the discussion as long as human life is still going on all the time. This is because humans have a capacity that always encourages them to think, and they realize that they are aware of their weaknesses and ignorance. AlQur’an itself also explains that humans are human beings created by Allah. There are various kinds of human advantages that Allah gave him, and it is not owned by other creatures. Therefore, this article will explain the human concept which is closely related to Islamic education, including the relationship between humans and the goals of Islamic education, and the relationship between humans and the content in the Islamic education curriculum. Thus, the effort to develop all the natural potentials that exist in humans, in order to keep developing under the conditions of human nature, is through education based on Islamic values.